2018
DOI: 10.1038/s41598-018-35418-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between neonatal vitamin D status and risk of schizophrenia

Abstract: Clues from the epidemiology of schizophrenia, such as the increased risk in those born in winter/spring, have led to the hypothesis that prenatal vitamin D deficiency may increase the risk of later schizophrenia. We wish to explore this hypothesis in a large Danish case-control study (n = 2602). The concentration of 25 hydroxyvitamin D (25OHD) was assessed from neonatal dried blood samples. Incidence rate ratios (IRR) were calculated when examined for quintiles of 25OHD concentration. In addition, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 42 publications
3
73
0
1
Order By: Relevance
“…This fits to the environmental risk factors that have been described for schizophrenia, like season of birth [171] and latitude [172]. Also a link between neonatal vitamin D levels and the schizophrenia risk was reported [173]. A recent randomized, placebo-controlled study from Krivoy and colleagues examined psychosis severity, mood, cognition, and metabolic profile in 47 schizophrenia patients during an 8-week supplementation of 14,000 IU vitamin D/week.…”
Section: Neuropsychiatric Diseasessupporting
confidence: 65%
“…This fits to the environmental risk factors that have been described for schizophrenia, like season of birth [171] and latitude [172]. Also a link between neonatal vitamin D levels and the schizophrenia risk was reported [173]. A recent randomized, placebo-controlled study from Krivoy and colleagues examined psychosis severity, mood, cognition, and metabolic profile in 47 schizophrenia patients during an 8-week supplementation of 14,000 IU vitamin D/week.…”
Section: Neuropsychiatric Diseasessupporting
confidence: 65%
“…Vitamin D deficiency is common in those with established psychiatric disorders, as a consequence of reduced outdoor behaviour 63,64 . It is feasible that the observed association between 25OHD concentration in blood spot samples taken at birth with later-life increased risk of schizophrenia 13,65 could be confounded by outdoor behaviour of mothers, which may be correlated with the mother's genetic liability to schizophrenia. While we find no evidence to support the hypotheses that variants associated with low 25OHD concentrations were associated with any of the selected phenotypes, we note that there is a linearity assumption in our Mendelian randomization analyses.…”
Section: Discussionmentioning
confidence: 99%
“…We present models that explore the genetic/causal relationship between body mass index (BMI) and 25OHD (high BMI is associated with lower 25OHD concentration in observational studies) 12 . Because we have an interest in the association between 25OHD and mental disorders 13 , we use Mendelian randomization methods to investigate the 6 bidirectional association between 25OHD and psychiatric disorders, as well as with a wider range of traits and diseases. Additionally, we present a GWAS to identify loci associated with variance in 25OHD (i.e., variance quantitative trait locus (vQTL) analysis) which can identify putative genotype environment interactions without prior identification of the environmental effect 14 .…”
Section: Introductionmentioning
confidence: 99%
“…We believe also that more epidemiological data needs to be collected to accurately assess the relationship between serum retinol concentration and schizophrenia. Previous work using dried neonatal blood spots has demonstrated that neonatal vitamin D deficiency was associated with later-life schizophrenia [121]. This approach could also be applied in this context to large cohorts for which blood spots are available, as retinol can be accurately assayed from dried blood [122,123].…”
Section: Future Directionsmentioning
confidence: 99%